UPAYA MENINGKATKAN HASIL BELAJAR SEJARAH KEBUDAYAAN ISLAM MATERI DAKWAH NABI MUHAMMAD SAW DI MAKKAH DENGAN METODE INSIDE OUTSIDE CIRCLE (IOC) SISWA KELAS VII MTs AL-MU’MIN DOGANG - Adilia Pradilla; Zaifatur Ridha; Nurmisda Ramayani (Jurnal Iqtirahaat, 2023)
This research is motivated by the fact that student learning outcomes are still low in SKI subjects at MTs Al-Mu'min Dogang. This is caused by the application of inappropriate learning methods. Based on the results of initial observations, it was revealed that there are problems that often arise, such as students being less active in SKI learning activities, students' lack of understanding of the material being taught, learning is still dominated by teachers and innovative learning has not been implemented in class. This study aims to determine the application of the inside outside circle method in improving student learning outcomes in SKI lessons in class VII MTs Al-Mu'min Dogang. This study used a class action research (PTK) method. The subjects of this study were class VII students of MTs Al-Mu'min Dogang, totaling 56 students. The application of the inside outside circle learning method in SKI lessons about the Da'wah of the Prophet Muhammad in Makkah to class VII students of MTs Al-Mu'min Dogang. Classroom action research conducted in Cycle I and Cycle II to apply the inside outside circle learning method to SKI lessons has proven to improve student learning outcomes. This can be seen from the results of the completeness percentage of student learning outcomes in Cycle I of 53.57% and increased in Cycle II of 87.5%. So it can be concluded that the application of the inside outside circle learning method can improve student learning outcomes in SKI lessons in class VII MTs Al-Mu'min Dogang.